Putative pheromones from the anal glands of male blennies attract females and enhance male reproductive success. - Barata, Eduardo N. (2008)
Parental males of several blenniid species have a pair of glands on the anal fin. These are thought to be a source of pheromones for female attraction and/or of antimicrobials for egg protection. In Salaria pavo, we tested the female attraction hypothesis and whether the anal glands are essential for egg parental care. In S. pavo and Salaria fluviatilis, we tested whether anal glands affect female mate choice. In a Y-maze, reproductive females were attracted to water conditioned by males with anal glands and macerated anal glands but not to substances released by conspecific females, water conditioned by males that had the anal glands removed or to macerated anal fin rays. Females preferred to spawn in nests of males with anal glands than in those of males without anal glands. In the laboratory, neither hatching success nor development time was affected by the removal of the anal glands from parental males. In contrast, most of the eggs without parental care did not complete their development. We suggest that the anal glands are specialized in the secretion of a pheromone that attracts reproductive females, and blenniids have evolved true chemical communication, possibly through the selective pressure of female mate choice.